The relationship of dietary patterns, and behavior of MP-ASI with nutritional status in children aged 6-12 months in Cigeulis Village, Banten Province - Zulva Velda Yanti; Mohammad Furqan; Izna Nurdianty Muhdar (Sarana Ilmu Indonesia (salnesia), 2024)
The growth of children in infancy is very rapid. If at this time the toddler's nutritional needs are not met, it will cause disturbances in the growth and development of toddlers. Underweight in toddlers occurs as a result of acute malnutrition. In the long term, children with underweight will experience cognitive impairment, decreased learning achievement, behavioral disorders, and increase the risk of death. Nutritional status in children can be influenced by several factors such as maternal knowledge regarding nutrition, diet, and complementary feeding behavior. The purpose of this study was to determine the relationship between nutritional knowledge, diet, and complementary feeding behavior with nutritional status at the age of 6-12 months in Cigeulis Village, Banten Province in 2022. This study was conducted in February-July 2022. The number of samples is 38 babies and baby mothers. This research has a cross-sectional design. Data were collected by measuring body weight and interviewing questionnaires to determine nutritional knowledge, eating patterns, and complementary feeding behavior. The results showed that 65.8% of toddlers had normal nutritional status, 65.8% of mothers had good nutritional knowledge, and 63.2% demonstrated appropriate complementary feeding practices. The dietary patterns of toddlers indicated adequate energy intake (65.9%), protein intake predominantly in the excessive category (47.4%), insufficient fat intake (60.5%), and adequate carbohydrate intake (50%). There was a significant association between complementary feeding practices and the nutritional status of toddlers. However, no significant relationship was found between energy, protein, and fat intake and the nutritional status of toddlers. In contrast, carbohydrate intake was significantly associated with the nutritional status of children under five (p<0.05).